2017
DOI: 10.1139/apnm-2016-0439
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training prior to myocardial infarction increases cardiac GLUT4 and partially preserves heart function in spontaneously hypertensive rats

Abstract: We assessed cardiac function (echocardiographic) and glucose transporter 4 (GLUT4) expression (Western blot) in response to 10 weeks of aerobic training (treadmill) prior to acute myocardial infarction (AMI) by ligation of the left coronary artery in spontaneously hypertensive rats. Animals were allocated to sedentary+sham, sedentary+AMI, training+sham, and training+AMI. Aerobic training prior to AMI partially preserves heart function. AMI and/or aerobic training increased GLUT4 expression. However, those anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Following an experimentally-induced acute MI, SHR showed a reduction in cardiac output, LVEF, LVSF and ventricular fractional area change (FAC). These series of parameters is consistent with that assessed in other studies by our research group [6, 8, 16] and others as well [26, 27]. In addition, the reduction in cardiac function may be largely explained by increased protein oxidation (augmented carbonyl levels) and D3 activity in cardiac tissue sample of the infarcted animals [3].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Following an experimentally-induced acute MI, SHR showed a reduction in cardiac output, LVEF, LVSF and ventricular fractional area change (FAC). These series of parameters is consistent with that assessed in other studies by our research group [6, 8, 16] and others as well [26, 27]. In addition, the reduction in cardiac function may be largely explained by increased protein oxidation (augmented carbonyl levels) and D3 activity in cardiac tissue sample of the infarcted animals [3].…”
Section: Discussionsupporting
confidence: 90%
“…Myocardial infarction was induced according to a procedure previously performed in our laboratory [6, 16]. Briefly, animals were placed in the dorsal decubitus position and anaesthetized with isoflurane (100mL, Cristália).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…69,70 Another mechanism is postulated to reflect angiogenesis in working muscles mediated by β-adrenergic stimulation of capillary growth by vascular endothelial growth factors and platelet-derived growth factors. 71 These processes are both stimulated by insulin-like-growth-factor-1, expressed proportionally with ET, and have been shown to reverse adrenergic related cardiac remodeling in animal models.…”
Section: Effects Of Et On CV Physiologymentioning
confidence: 99%
“…Additionally, ET favorably impacts cardiac remodeling and results in improvements of the performance of the myocard [41]. The mechanisms are; reversal of metabolic decoupling processes with decreases in glucose uptake in patients with metabolic syndrome and postulation of angiogenesis in working muscles mediated by βadrenergic stimulation of capillary growth by vascular endothelial growth factors and platelet-derived growth factors [42][43][44]. More recent studies have shown that ET-associated post-transcriptional gene regulation via micro-RNA reduce remodeling through interactions among metabolic, contractile and epigenetic genes [45].…”
Section: Effects Of Exercise Training On Cardiovascular Physiologymentioning
confidence: 99%